ESTADO DE LA EDUCACIÓN Y FORMACIÓN EMPRESARIAL EN LOS PAÍSES Y REGIONES ESPAÑOLAS DEL GEM - Ana Fernández Laviada; Lidia Sánchez Ruiz (Revista de Estudios Empresariales. Segunda Época, 2014)
Specialised literature presents education and training as a determining factor for entrepreneurship. However, time and time again experts at the Global Entrepreneurship Monitor (GEM) have stated that it’s one lowest, and sometimes the least, valued elements in this area. Therefore, the objective of this study is to analyse the state of entrepreneurship education and training in its different stages within the countries and regions that participated in GEM 2012. Specifically, what is sought is, based on the opinion of the experts, the state of entrepreneurship training and education in each level analysed in GEM, generically as well as by country, while looking at the possible differences (strengths and weaknesses) that appear in each one. Furthermore, this is paired with a national analysis that examines the situation of the different participating regions in the study. In order to carry out the analysis, the 2012 NES database is used. In that edition, a total of 69 countries participated and, in the case of Spain, there were 14 regions all with 36 experts in each. The data processing is carried out using the Rasch model for measurement. The preliminary results show that, in general, university level education geared towards entrepreneurship is more highly developed than at the lower levels of education, such as in secondary and primary education. Nevertheless, the individual analysis makes it possible to detect differences between countries and regions.